PERANCANGAN SISTEM INFORMASI PENJUALAN PERALATAN HIKING BERBASIS DESKTOP PADA TOKO CIMONE OUTDOOR TANGERANG - Eka Wulansari Fridayanthie (Jurnal Khatulistiwa Informatika, 2015)
In today's era of globalization, information technology and computers will play a decisive role in business competition. Success in mastering information technology will determine the company's success in competing. With the development of information technology and computers are very fast, the use of computer technology to be very effective when applied to a company, organization or government agency. The system is designed with object-oriented methodology, and implemented using language pemerograman Visual Studio 2005 and Microsoft Office Access as its database. Results from this study can be concluded that the system that created this information can allow a user to resolve minor problems that often occur without the help helpdesk.Keyword: Business Applications, Sales Activities, Information Systems